MODEL OF IMPROVING PERFORMANCE MANAGEMENT PRACTICE BASED EMPLOYEE PERFORMANCE MEDIATED BY EMPLOYEE WORK ATTITUDE - Mena Qomari; Ibnu Khajar (IJIBE (International Journal of Islamic Business Ethics), 2017)
The present study intended to test a model in which performance management practice and Islamic  values  predict  work  attitude  and employee performance. A total of 100 respondents completed questionnaires on performance management practice, employee work attitude, Islamic values, and employee performance. The results from structural  equation  modeling  based  smartPLS  3.0  confirmed that 1) performance management practice is positively related to work attitude and employee performance; 2) work attitude is positively related to employee performance; and 3) Islamic values moderates the relationships between work attitude and employee performance. Keywords : Performance management practice, Work attitude, Islamic values, Employee performance